Development of optical sensor system and hardware base frame for checking the light and radiation fields of a linear accelerator. (1st November 2022) - Lee, B.; Kang, S.W.; Kim, J.Y.; Lee, J.; Kim, H.J.; Kim, W.C.; Song, C.; Eom, K.Y.; Kim, I.A.; Kim, J.S.; Chung, J.B.
Abstract: This study aims to quantitatively evaluate the light and radiation fields of a linear accelerator by developing an optical sensor quality assurance (QA) system using a cadmium sulfide (CdS) photodetector cell and a hardware base frame manufactured in-house. The CdS photodetector cell used as the optical sensor has a size of 3.4 × 4.1 mm 2, can measure up to 100 lux of light, and has a response time of approximately 20 to 30 ms. To check the alignment of the light field, it was manufactured with a CdS cell optical fiber holder, and the microcontroller board and control module were configured to scan the light field profile. Additionally, for accurate operation of the sensor, it was programmed using the integrated development environment (IDE) sketch. The alignment check of the radiation field was analyzed using the image data measured with electronic portal imaging device (EPID) using the manufactured hardware base frame. An analysis program written in MATLAB was used to evaluate the alignment of the radiation field. For symmetric fields measured using the optical sensor QA system, the full width at half maximum (FWHM) values of crossline (X) and inline (Y) profiles were 100.391 mm and 98.725 mm, respectively, for a field size of 100 × 100 mm 2, and 199.093 mm and 198.886 mm, respectively, for a field size of 200 × 200 mm 2 . The X and Y FWHM values measured by the sensor system for the light fields were within 1 mm of the field size of the visual inspection. In addition, the FWHM value of the asymmetric radiation field measured using the fabricated frame and EPID was measured from the center bearing ball of the field to the bearing ball in each field of the four directions in the EPID image, and when the X1, X2, Y1, and Y2 jaws were opened by 50 mm, FWHM values were 50.120 mm, 50.240 mm, 48.860 mm, and 49.870 mm, respectively. The corresponding values were 99.520 mm, 99.570 mm, 99.010 mm, and 99.880 mm when the jaw fields were opened by 100 mm. The optical sensor system and hardware base frame developed in this study demonstrated the ability to evaluate both light and radiation fields more simply and quantitatively when compared to the conventional QA process. This QA system will provide medical physicists with more reliable QA results than the conventional QA method that uses graph paper and film.